Mediating Cultures: a Study of Translation Strategies in the French Translation of Ashok Ferry’s “The Ceaseless Chatter of Demons” - Jayawardena, Samanthi (Respectus Philologicus, 2026)
Translating a source text brings out various challenges. The translators constantly seek strategies to overcome the constraints they encounter. The present study aims to identify obstacles and analyse the strategies employed to address them. The chosen text, Ashok Ferry’s The Ceaseless Chatter of Demons (2016), is complex, given that it’s written in Sri Lankan English and it’s set in a culturally rich context. It was translated into French in 2018. Following Mona Baker’s (2011) common types of non-lexical equivalence at the word level, the study identifies forty-two challenging terms. To identify and analyse the strategies employed in the source text, the study draws on Baker’s (2018) explanation of the strategies used by professional translators. The study identifies five strategies for translating different lexical types. The same strategy is used for multiple lexical types, but its effectiveness varies. Though limitations are highlighted in the study, the strategies prove necessary for negotiating cultural differences.